Physiological and pathological roles of Ang II and Ang- (1-7) in the female reproductive system - Liu, Yuanyuan; Hao, Haomeng; Lan, Tingting; Jia, Rui; Cao, Mingya; Zhou, Liang; Zhao, Zhiming; Pan, Wensen (Frontiers in Endocrinology, 2022)
The local Renin-Angiotensin System (RAS) has been demonstrated to exist in a wide range of tissues and organs, In the female reproductive system, it is mainly found in the ovary, uterus and placenta. The RAS system is made up of a series of active substances and enzymes, in addition to the circulating endocrine renin-angiotensin system. The active peptides Angiotensin II (Ang II) and Angiotensin (1-7) (Ang-(1-7)), in particular, appear to have distinct activities in the local RAS system, which also controls blood pressure and electrolytes. Therefore, in addition to these features, angiotensin and its receptors in the reproductive system seemingly get involved in reproductive processes, such as follicle growth and development, as well as physiological functions of the placenta and uterus. In addition, changes in local RAS components may induce reproductive diseases as well as pathological states such as cancer. In most tissues, Ang II and Ang- (1-7) seem to maintain antagonistic effects, but this conclusion is not always true in the reproductive system, where they play similar functions in some physiological and pathological roles. This review investigated how Ang II, Ang- (1-7) and their receptors were expressed, localized, and active in the female reproductive system. This review also summarized their effects on follicle development, uterine and placental physiological functions. The changes of local RAS components in a series of reproductive system diseases including infertility related diseases and cancer and their influence on the occurrence and development of diseases were elucidated. This article reviews the physiological and pathological roles of Ang II and Ang- (1-7) in female reproductive system ,a very intricate system of tissue factors that operate as agonists and antagonists was found. Besides, the development of novel therapeutic strategies targeting components of this system may be a research direction in future.